Nina Milgichil tells Amchekh story - Lena Sotrudinkova; Valentina Dedyk (Alexander King, 2013)
Nina tells a story she learned from Amchekh. She said that she included a lot of Koryak words to make it more understandable. Sitting in her living room. Nina comments on a few of the words she used. Defines some. Ambient sound recording for this session. Born Kollegova. One of Valentina Romanovna's early students in the Peduchilishche. She has 5 children, the youngest born around 2011. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.